Real Effects of Common Currencies in East Asia - Shirono, Kazuko (Washington, D.C. : International Monetary Fund, 2007)
Since the 1997 Asian currency crisis, new interest has emerged in the formation of a common currency area in East Asia. This paper provides estimates of trade and welfare effects of East Asian currency unions, using a micro-founded gravity model. Counter-factual experiments to assess the effects of various hypothetical currency arrangements for East Asia suggest that an East Asian currency union will double bilateral trade in the region, but the resulting welfare effects will be moderate. However, if Japan, a major trade partner for East Asia, is included in the union, welfare effects increase substantially. The evidence thus suggests that certain regional currency arrangements in East Asia will stimulate regional trade rigorously and can generate economically significant welfare gains.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet